(3TQM eHMK GdGSJUMGH ef aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg gh dZI CNP GdTjA gPG GSJajOg ef GdSjf hGdJGA (B... (3bhdg hefg CHQ hef GdGSJUMGH HeYfi GdCNP bhdg GHbGA eG cGf hEfeG cGf gPG CSOgG dCfg GTJed Ydi GQcGf GdGSJUMGHs
(3BNQgG (B:s
(3BNQgG(B: (3hGdebOeI GdChdi Cf GdTc aj GdQGaY EfeG jchf Ydi JbOjQ GdGbJVGA hEdG adG jchf Tc aj GdQGaY Hd aj GdebJVi h M adG jchfs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs